Simulating the Spatial Mismatch between Ecosystem Services’ (ESs’) Supply and Demand Based on Their Spatial Transfer in Urban Agglomeration Area, China - Liu, Min; Fan, Jianpeng; Li, Yuanzheng; Sun, Linan (Land (Basel), 2022)
Ecosystem service spatial transfer is considered a feature that can deliver ecosystem services at a distance to meet the demands in areas with uneven spatial distribution of natural and social economic development. The natural ES spatial transfer distance and intensity were simulated by using the modified breaking point model in the Central Plains urban agglomeration (CPUA) with the cities of Luoyang, Zhengzhou, Shangqiu, and Huaibei stretching across. It is shown that there is a spatial mismatch between ES supply from ecospace and its demands from cities; relying only on natural spatial transfer, none of the ESs of the ecospace can be transported to corresponding population centers; and a spatial gap between ES supply and demand is illustrated in urban agglomeration areas. Intercity cooperation in ecosystem management and landscape planning based on ES spatial transfer would be good choices for cities, giving full play to comparative advantages to achieve sustainable development for the entire CPUA.